Persistensi Post-Divorce Women from the Perspective of Islamic Law - Wirda Garizahaq; Syafuri Syafuri; Hudaeri Hudaeri; Itang Itang (Bulletin of Community Engagement, 2026)
The divorce in Islamic family law is not merely the termination of a marital bond, but a legal event that produces continuing responsibilities regarding maintenance, dignity, child care, and access to justice. This article examines the gap between the normative recognition of post-divorce rights and their practical fulfillment in Indonesia’s Religious Courts. The study uses normative legal research supported by qualitative document analysis. Primary legal materials include Islamic family law norms, the Marriage Law, the Compilation of Islamic Law, Supreme Court regulations, and human rights instruments. Secondary materials include classical fiqh, maqasid al-shari’ah scholarship, legal protection theory, legal system theory, and empirical studies from 2017-2025. The analysis shows that iddah maintenance, mut’ah, unpaid dower, child maintenance, and hadhanah should be interpreted as instruments of substantive protection rather than discretionary generosity from former husbands. Empirical studies indicate that women’s post-divorce rights often fail because of limited legal literacy, patriarchal legal culture, passive pleadings, inconsistent ex officio judicial authority, and weak enforcement mechanisms. This article argues that post-divorce protection must move from textual entitlement to executable justice through gender-sensitive adjudication, clear rulings, salary deduction mechanisms, institutional interconnection, and community-based legal assistance. In maqasid terms, the protection of divorced women safeguards life, property, lineage, dignity, and family continuity.